2004
DOI: 10.1097/00129039-200412000-00005
|View full text |Cite
|
Sign up to set email alerts
|

CYP2E1 Polymorphism, Cigarette Smoking, p53 Expression, and Survival in Non-small Cell Lung Cancer

Abstract: The expression of selected gene products involved in cell differentiation and cell growth and genetic polymorphism of detoxifying genes was examined in 105 surgically resected nonsmall cell lung cancer (NSCLC) patients, and the relationship of these factors was correlated with cigarette smoking and patient survival. Genotyping of peripheral blood lymphocytes from 87 patients was performed for CYP2E1, GSTM1, GSTT1, mEH, and MPO detoxifying genes using polymerase chain reaction. Formalin-fixed, paraffin-embedded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 29 publications
0
20
1
Order By: Relevance
“…Likewise, the recent results of Karacaoğlan et al 9 on the CYP2E1*5B polymorphism are also in line with the findings of Li et al 18 , both in regard to response to chemotherapy and survival. However, their findings are in contrast to those of Oyama et al 24 and Haque et al 25 in respect to survival. The findings of Karacaoğlan et al 9 in regard to the effect of CYP2E1*6 polymorphism on survival also coincided with the results of Przygodzki et al 23 The only study for the CYP2E1*7B polymorphism on this issue was reported by Karacaoğlan et al 9 who observed no association between the CYP2E1*7B polymorphism and response to chemotherapy and survival in patients with NSCLC.…”
Section: The Associations Between Cyp Polymorphisms and Response To Ccontrasting
confidence: 61%
See 1 more Smart Citation
“…Likewise, the recent results of Karacaoğlan et al 9 on the CYP2E1*5B polymorphism are also in line with the findings of Li et al 18 , both in regard to response to chemotherapy and survival. However, their findings are in contrast to those of Oyama et al 24 and Haque et al 25 in respect to survival. The findings of Karacaoğlan et al 9 in regard to the effect of CYP2E1*6 polymorphism on survival also coincided with the results of Przygodzki et al 23 The only study for the CYP2E1*7B polymorphism on this issue was reported by Karacaoğlan et al 9 who observed no association between the CYP2E1*7B polymorphism and response to chemotherapy and survival in patients with NSCLC.…”
Section: The Associations Between Cyp Polymorphisms and Response To Ccontrasting
confidence: 61%
“…For example, studies on the CYP2E1*5B polymorphism are rather conflicting. Oyama et al 24 found an increase in survival in mutant allele carriers, whereas Haque et al 25 observed shorter survival in mutant carriers, and Li et al 18 found no association between this CYP gene polymorphism and survival in patients with NSCLC. Przygodzki et al 23 reported no significant association between the CYP2E1*6 polymorphism and survival in patients with NSCLC.…”
Section: The Associations Between Cyp Polymorphisms and Response To Cmentioning
confidence: 99%
“…Emerging evidence, although inconclusive, has shown that TP53 (Arg72Pro) polymorphism is not only associated with lung cancer risk but also influences patient response to platinum-based chemotherapy and survival (28)(29)(30)(31)(32)(33). Furthermore, associations have also been shown between polymorphisms of some CYP genes such as the CYP2E1 or CYP1A1 and TP53 gene in NSCLC (5,6,9,34,35).…”
Section: Introductionmentioning
confidence: 99%
“…In a review of the literature, Lee et al (2002) did not find a consistent change in the carcinogenic effect of smoking according to mEH polymorphisms. However, Cajas-Salazar et al (2003) found that smokers carrying the high-activity form of mEH had a higher risk of lung cancer, and Haque et al (2004) found no effect of mEH polymorphisms on survival in smokers. As would be expected from the mouse studies with benzene, Garte et al (2008) discovered that subjects with the genotype for fast catalytic conversion of benzene, a bioactivation process, had an increased genetic susceptibility as determined by measurement of single-strand breaks in DNA.…”
Section: Discussionmentioning
confidence: 99%